Dredging and Dredged Material Placement - Randall, Robert E (American Society of Civil Engineers (ASCE), 2022)
This book provides a comprehensive overview of the current state of dredging. Author imparts his extensive knowledge of the subject using descriptions, examples, definitions, and problems. Topics include: Dredging history; Basic fluid mechanics for dredging; Dredging equipment; Dredge pumps, modeling, and cavitation; Characteristics of dredged sediments; Pipeline transport of sediments; Cutters, dragheads, and buckets; Production estimation; Dredge instrumentation and automation; US environmental laws and permitting process; Dredged material placement; Contaminated sediments and capping; Dredging costs estimation; Dredging operations; and Dredging research, training, and education. Randall's book intends to provide a thorough summary of dredging and dredged material placement to interested students, practicing engineers, consultants, and scientists.